A Several-Kilometer-Long Archosaur Route in the Triassic of the Swiss Alps - Cavin, Lionel; Piuz, André (Frontiers in Earth Science, 2020)
The Mesozoic sedimentary cover of the Aiguilles Rouges Massif straddling the Swiss-French border has yielded several archosaur footprint sites dated to the Early or Middle Triassic and composed of mostly poorly preserved footprints lacking any orderly arrangement and resting on a megatracksite level. Here we describe two short archosaur trackways attributed to Isochirotherium herculis and located at ca. 2400 m asl in two distinct small valleys separated from each other by a linear distance of 6.4 km. Projection of both trackways onto the same plane showed that they were aligned with a deviation angle of only 3 degrees. These aligned trackways are interpreted as remnants of a straight and narrow walking route taken by a single trackmaker species. It is possible that both trackway segments were made by the same individual. In the present landscape, the Triassic outcrops are small and scattered along a roughly straight NE-SW line. The orientation of the trackways agrees with the general orientation of the outcrops, which is very unlikely to be caused by chance only. We explain this apparent coincidence as resulting from the structural inheritance of a general NE-SW Paleozoic shear zone that controlled the orientation of the Vindelician High on which the archosaurs walked, then that defined the axis of the much later Massif uplift, and eventually affected the general orientation of the erosion that uncovered the trackways.